PANGAN TOYYIBAH : MENGENALKAN PERSPEKTIF GAYA HIDUP SEHAT UNTUK PENDIDIKAN ANAK USIA DINI - Wahju Dyah Laksmi Wardhani; Tri Endang Jatmikowati; Angraeny Unedia Rahman (Pendidikan Guru PAUD, FKIP, Universitas Muhammadiyah Tasikmalaya, 2019)
Abstrak This article offers a new construction of learning perspective about healthy food for early learners. To date, the term of healthy food has been introduced in early childhood education as a balanced nutritious food known as a “4 Sehat 5 Sempurna and Halal”. The consumption patterns, kinds and variations of meals of a child are mostly managed by parents or influenced by the environment.The new perspective is emphasized more on the concept of the